Probleme der Erhebung von Nutzungsstatistiken im Open Access - Becker, Pascal-Nicolas; Paulsen, Yannick (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2025)
Usage statistics generally require that automated accesses are disregarded and only accesses initiated by a person are counted for the statistics. For closed access content, access is restricted to certain identified groups, for example by using designated IP address ranges or single sign-on solutions. Many bots therefore have no access in closed access or can be easily recognized based on authentication. Open Access ensures that content can be used without technical or other barriers. Therefore, for Open Access content, bots cannot be identified in a tamper-proof manner. In addition, content in Open Access can also be distributed by others, which means that there may be further copies of the work on other servers that cannot be counted. It is therefore not possible to keep reliable usage statistics for Open Access content. This article focuses on Open Access repositories as an example, but the underlying problems with usage statistics apply to all kind of Open Access publications, including publisher publications in Open Access.
Keywords: Open Access; Usage statistics; Bbliometry; Repositories